Grade-School Children's Social Collaborative Skills: Links With Partner Preference and Achievement. (February 2014) - Ladd, Gary W.; Kochenderfer-Ladd, Becky; Visconti, Kari Jeanne; Ettekal, Idean; Sechler, Casey M.; Cortes, Khaerannisa I.
Little is known about the skills children need to successfully collaborate with classmates on academic assignments. The purposes of this study were to identify grade-schoolers' collaborative skills, evaluate the importance of identified skills for collaborative work, and determine whether differences in skill use were related to children's social and scholastic competence. Initially, third through fifth graders ( N = 113) described attributes of "good" collaborators, and these attributes were distilled into distinct skill categories or "types." Next, third through fifth graders ( N = 212) rated exemplars of each skill type as a basis for skill importance and peers' skill use and provided data that were used to construct measures of work partner preference and peer acceptance. Teachers reported on participants' achievement in multiple academic domains. Four categories of work-related and interpersonal skills were identified, and these skill types were differentially associated with children's work partner preferences, peer acceptance, and achievement. Overall, the findings help to specify the types of skills grade-schoolers need to relate effectively with classmates in the context of collaborative academic tasks.